2021
DOI: 10.1080/0886022x.2021.1936040
|View full text |Cite
|
Sign up to set email alerts
|

ATF4-dependent heme-oxygenase-1 attenuates diabetic nephropathy by inducing autophagy and inhibiting apoptosis in podocyte

Abstract: Aim: Podocyte injury plays an important role in diabetic nephropathy (DN), yet the underlying molecular mechanisms of podocyte injury in DN is not clear. Here, we investigated the role of activating transcription factor 4 (ATF4) and HO-1 in DN-induced podocyte injury. Methods: Protein expression was measured by western blotting (WB) and immunofluorescence. Cellular apoptosis was quantified by flow cytometry. ATF4 siRNA knockdown and HO-1 overexpression in podocyte were employed to evaluate the role of ER stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…Here, we confirm that the induction of DN caused a mild increase in renal HO-1 activity and protein expression, probably as a feedback mechanism to protect the kidney against DN hazards. Our findings were in line with several previous studies reporting similar increase in HO-1 activity and expression in diabetic animal models [ 6 , 50 , 51 , 52 , 53 ]. One study reported, in contradiction with our results, that diabetic high-fat-diet/STZ-treated mice kidneys showed a decrease in HO-1 expression [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Here, we confirm that the induction of DN caused a mild increase in renal HO-1 activity and protein expression, probably as a feedback mechanism to protect the kidney against DN hazards. Our findings were in line with several previous studies reporting similar increase in HO-1 activity and expression in diabetic animal models [ 6 , 50 , 51 , 52 , 53 ]. One study reported, in contradiction with our results, that diabetic high-fat-diet/STZ-treated mice kidneys showed a decrease in HO-1 expression [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Still, the oxidative, inflammatory, and apoptotic pathways intermingle with high complexity making it difficult to highlight a distinct cause–effect relationship between them [ 5 ]. Recently, the heme oxygenase pathway has also been implicated to have a role in DN by reducing podocyte autophagy and diminishing apoptosis [ 6 ]. Traditionally, the initial diagnostic sign of DN is albuminuria, with urinary albumin of 30–299 mg/g creatinine indicative of early nephropathy, and more than 300 mg/g creatinine signifying overt nephropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated for the first time that CRP is able to modulate the balance of apoptosis and autophagy in podocyte autophagy. Many studies including ours have reported the crucial role of CRP in accelerating apoptosis, 10,55 and crosstalk between apoptosis and autophagy has been confirmed that it can participate in the occurrence of DKD, 23,24 suggesting CRP is reasonable to participate in the pathogenesis of DKD. Moreover, considering that C3a is a multifunctional factor in inflammation, chemotaxis and cell activation, 43,44 we detected the direct effect of C3a on podocyte autophagy under high‐glucose conditions in vitro, and C3a‐induced podocyte autophagy under high‐glucose conditions was established in our study.…”
Section: Discussionsupporting
confidence: 56%
“…Autophagy and apoptosis are two major cellular processes that determine cell fate under both physiological and pathological conditions, and mounting evidence indicates that their balance plays a pivotal role in the development and progression of DKD. [22][23][24] Autophagy is an intracellular "self-eating" pathway by which dysfunctional proteins and organelles are degraded and recycled to maintain cellular homeostasis and cell integrity. 25,26 Apoptosis is a natural programmed cell death process in which orderly cell death is controlled by genes as a means to better adapt to the living environment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the complicated pathogenesis of DN, podocyte injury has been identified to play essential roles [ 3 ]. Structural changes or damage to podocytes are associated with kidney injury, resulting in proteinuria and severe renal insufficiency, and eventually leading to DN [ 4 ]. Furthermore, impaired podocytes lead to impaired selective glomerular filtration and contribute to the formation of proteinuria [ 5 ].…”
Section: Introductionmentioning
confidence: 99%